Pegylated interferon de novo-induce autoimmune haemolytic anaemia in chronic hepatitis C patient - Said, Ashraf (BMJ Publishing Group, 2011)
A 55-year-old Egyptian woman with chronic hepatitis C undergoing treatment with pegylated interferon (Peg-IFN) alfa-2a plus ribavirin was referred to our hospital on November 2010 with prolonged easy fatigability and an attack of syncope; she had no prior history of autoimmune disorders or allergy. Laboratory investigations documented the presence of Peg-IFN induced autoimmune haemolytic anaemia and autoimmune thyroiditis. Intravenous γ globulin (IVGG) failed to correct the autoimmune process; on the other hand steroid therapy dramatically corrected both haematological and thyroid values, and step down the immune process. Our report indicated that Peg-IFN de novo-induce autoimmune haemolysis, documenting a previous report. IVGG failed to step down the immune process in our case.